(untitled) (Journal of Plant Disease Sciences, 2020)
Blue mold of apple is caused by Penicillium expansum Link. Thom. Ex. is one of the important serious post harvest disease in India. Total twenty five isolates of P. expansum were isolated from post harvest infected apple fruits for sensitivity tested against fludioxonil on Potato Dextrose Agar (PDA) medium. Sensitivity of these isolates to fludioxonil was determined using food poisoning technique. In vitro minimum Inhibition concentration (MIC) for fludioxonil was determined; isolate Pe-11 MIC-760.6µg/ml was sensitive while isolate Pe-16 MIC-975.3µg/ml was resistant. In vivo Pe-11 MIC 1825.2µg/ml was sensitive. Pe-16 MIC-2375.5µg/ml was tolerant. fludioxonil resistant mutant (Pe-EMS-12, MIC 4775.8µg/ml) is equally important to manage using different fungicides. P. expansum was tested against fludioxonil and other fungicides viz. propiconazole, captan, difenoconazole, hexaconazole, dithiocarbmate, thiobendazole and diphenylamine. In vitro experimental results revealed that the percentage control efficacy (PCE) values range at 50% Conc. (45.00 – 50.01%) while at 100% Conc. (52.80- 63.56%) individually and in mixture with fludioxonil increased its PCE from at 50% Conc. (55.19 - 69.90%) while at 100% (68.67 -73.90%). In vivo PCE at 50% Conc. (52.50 - 57.90%) individual and mixture (58.12 - 62.25%) while at 100% from alone (57.32 - 72.32%) and in mixture (73.00 – 80.18%) PCE further increased and without fungicide served as control.